PENGELOLAAN PEMBINAAN KEDISIPLINAN PESERTA DIDIK DI SMK 1 MUHAMMADIYAH SANGATTA UTARA (Jurnal Sosial Humaniora dan Pendidikan, 2022)
The writing of this article is motivated by the problem of students who are less disciplined at school. The causal factors are fixed very variously. Consequently, this article aims to describe the management of student discipline development in SMK 1 Muhammadiyah. In writing, this article is a type of qualitative descriptive research. Data collection techniques using interviews, observation, and documentation. While the analysis tool is to uses data condensation, presenting data, and drawing and drawing conclusions. This study shows that the management of disciplinary development is contained in a corrective plan through steps that are applied to students with problems. Organizing is carried out in collaboration between BK teachers, student affairs, and homeroom teachers. Students often encounter implementation through socialization with various media or the right way. Supervision is carried out in two ways by the principal, namely field observations and receipt of weekly and monthly reports. Based on the explanation above, the role of school personnel in fostering student discipline at SMK 1 Muhammadiyah North Sumatra can primarily be categorized as "good" at this time. This research can be recommended to school personnel to pay more attention and monitor and provide discipline guidance to students to be more disciplined in school.